Audio-visual speech-in-noise tests for evaluating speech reception thresholds: A scoping review - Adeel Hussain; Adele M. Goman; Mandar Gogate; Kia Dashtipour; Jasper Kirton-Wingate; Zain Hussain; Aziz Sheikh; Michael A. Akeroyd; Amir Hussain (PLoS ONE, 2026)
Objective To evaluate the advancements in speech intelligibility testing over the recent decades, with a particular emphasis on the development of audiovisual speech in noise tests that incorporate both auditory and visual modalities for the measurement of speech recognition thresholds. Design A scoping review was conducted systematically to examine the existing literature on speech intelligibility testing methods. Following comprehensive screening process, studies were selected for detailed analysis, focusing on audiovisual integration and potential for remote or automated administration within studies methodologies. Study Sample The review encompassed 11 scholarly articles that investigated diverse approaches to speech intelligibility testing. Results The analysis revealed variability in the accuracy and reliability of speech intelligibility testing methods. Although certain methods demonstrated efficacy in incorporating audiovisual cues, none of the reviewed studies included provisions for remote administration, thereby necessitating the presence of a clinician for test execution. This limitation underscores the imperative for further research development of remote testing methodologies that leverage audiovisual technologies to assess speech in noise. Conclusions The findings of this review underscore the critical need for advancement in speech intelligibility testing methodologies particularly integrating audiovisual components and enabling remote administration. The development in this domain holds significant potential to enhance the assessment and implementation of assistive technologies for individuals with hearing impairments.